Elementary School Social Studies Learning Assessment Instrument - A. Gafar Hidayat; Astriani Aulia (Yayasan Insan Mulia Bima, 2024)
Assessment instruments are used as tools to collect data related to students' cognitive, psychomotor and affective competencies, as a basis for analysis and interpretation for decision making related to efforts that can be made to improve these abilities through the learning process. The research method used is qualitative descriptive research. In the learning process in the classroom, educators are not only facilitators, but also evaluators or appraisers to determine whether the goals have been achieved. Therefore, this article was written so that educators are expected to be able to create assessment instruments and carry out assessments from affective, cognitive and psychomotor aspects appropriately.